Social Interaction between Lecturers and Undergraduates in EFL Classrooms: A Case Study from a Thai University in the Age of AI - Boontong, Nattana; Omanee, Boonyarit; Phairot, Ekkapon; Khemanuwong, Thapanee (My University, 2025)
This explanatory sequential mixed-methods study investigates how artificial intelligence (AI) is reshaping social interactions in Thai EFL classrooms amid the rapid spread of chatbots and AI-supported writing tools in language education (2020–2025). Grounded in Sociocultural Theory and the Interaction Hypothesis, the design combined a questionnaire administered across four undergraduate year levels with semi-structured interviews of eight purposively selected students. Descriptive statistics summarized the survey responses, while the interview data was analysed thematically. The findings show that students welcome AI for quick access to input, idea generation, and building confidence before speaking yet remain cautious about accuracy and overreliance, and many still prefer lecturer clarification for complex issues. A new contribution emerges in the form of a dual effect: pre-class AI preparation enables students to enter lessons better prepared and more confident, but it is also associated with fewer spontaneous in-class clarification questions, suggesting a subtle displacement of routine lecturer–student interaction. While AI can stimulate participation and reduce hesitation, it cannot replace teacher guidance, formative feedback, and relational rapport. Overall, the evidence supports a hybrid interaction model in which AI-supported preparation is paired with human-led dialogue during class. Implications extend beyond ZPD and the negotiation of meaning toward a whole-class ecology: brief, transparent rules for responsible AI use (verification and disclosure), protection of talk time through AI-off/AI-critique moments, and process-oriented assessment that includes light evidence of AI use and short reflections on revisions. Program-level alignment (equity safeguards, approved tools, and privacy/ethics policies) is recommended to keep expectations consistent. By documenting both the benefits and displacement risks of pre-class AI use, this study refines the sociocultural theory for the AI era. It offers scalable guidance for EFL programs in Thailand and across Asia.
Keywords: AI in EFL; hybrid interaction model; lecturer–student interaction; social interaction